Application of Community Based Tourism (CBT) in the Development of Gosari Nature Tourism (Wagos) Gosari Village, Ujungpangkah District, Gresik Regency - Muhammad Hifdzi Rusydany; Tukiman Tukiman (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
The tourism industry in rural areas is able to have an impact on various aspects for both the community and the government. Tourism-based community and village participation is one form of effort to increase the tourism industry. This study aims to determine the application of Community Based Tourism (CBT) in the development of Gosari Nature Tourism (WAGOS) in Gosari Village, Ujungpangkah District, Gresik Regency. This study uses a descriptive qualitative approach. Community Based Tourism (CBT) is expected to play a significant role in the growth of Gosari Nature Tourism in Ujungpangkah District, Gresik Regency, and this research will provide an overall picture of its application in that context. Specifically, researchers used key informant data sources, places and events, and documents. Interviews, observations, documentation, and online data collection were used to collect information for this study, with the researcher acting as the main instrument integrated with the observed data sources. Data analysis techniques used are collection, data compaction, data presentation, drawing conclusions and verification. While the validity of the data used is triangulation and reference adequacy. The results of this study found that the planning stage had been carried out properly. Then in the implementation of the distribution of the portion of the implementation of Gosari tourism development it was divided into 3 parts. As well as the impact and benefits of the establishment of Gosari tourism are felt by the community starting from small things, namely a sense of pride and friendliness towards tourists. So that the application of CBT in Gosari Tourism has been carried out properly and optimally